Data Elicited Through Apps for Health Systems Improvement: Lessons From Using the myEXP Suite of Smartphone and Web Apps. Issue 1 (25th September 2018) - Miatello, Ashleigh; Mulvale, Gillian; Hackett, Christina; Mulvale, Alison; Kutty, Ashwin; Alshazly, Faten
A promising approach to meeting the need in many jurisdictions for timely, in-depth qualitative health systems experience data, is to elicit feedback through smartphone and web applications (apps). Apps offer an appealing tool to elicit data from patients and family members who may feel stigma when receiving some services and a power imbalance when providing feedback to health-care providers. In this article, we examine the effectiveness of a suite of smartphone and web apps called my Experience ( my EXP) that were created to gather care experiences of youth, family members, and service providers as part of an experience-based co-design (EBCD) study in Ontario involving youth with mental disorders. We analyzed data from 12 triads of youth (aged 16–24), family members, and service providers gathered between August 2015 and December 2016. We used qualitative content analysis to understand participant feedback on the my EXP apps and identify thematic categories that emerged from experience data elicited through the my EXP apps. We found overall that the my EXP apps were more effective at eliciting experience data from youth compared with family members and service providers. Rich experience data were gathered from youth about treatment plans in real time through the apps. The apps also showed important promise as reflective tools for all participants. They may offer advantages in research that seeks to improve responsiveness in service delivery and build mutual understanding. The apps also offer choice in how data are elicited, encourage more candid feedback and help to overcome stigma, which are important considerations for some vulnerable populations. For service redesign research using approaches such as EBCD, apps offer real-time data gathering that can complement and enhance traditional approaches such as retrospective interviews and observation.